Schistura phamhringi, a new stone loach from Chindwin Basin in Manipur, India (Cypriniformes: Nemacheilidae) - Shangningam, Bungdon; Lokeshwor, Yumnam; Vishwanath, Waikhom (Zootaxa, 2014)
Schistura phamhringi, new stone loach, is described from Dutah Stream, tributary of the Yu River (Chindwin basin), near Larong Village, Chandel District, Manipur, India. It is distinguished from all its congeners by a unique combination of characters: 6–7 black saddles, each continued on both flanks forming broad diamond-shaped black bars with narrow ventral margin; bars superimposed on a grey stripe along lateral line; upper lip with numerous melanophores; black basicaudal bar arc-shaped; complete lateral line; and prominent oar-like suborbital flap on male.